2019
DOI: 10.1111/psj.12315
|View full text |Cite
|
Sign up to set email alerts
|

Social Policy Perspectives on Economic Inequality in Wealthy Countries

Abstract: This essay reviews the policy‐oriented literature on economic inequality in wealthy countries published from 2008 to 2018. We focus on this decade because it is a period bookended by both the beginnings of the Great Recession of 2008–2009 as well as the recovery. During this timeframe, attention to inequality by social policy scholars grew substantially, which we argue reflects an interest in both inequality trends as well as redistributive social policy. We observe in the literature sustained efforts to under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 119 publications
(167 reference statements)
1
5
0
Order By: Relevance
“…According to participants, the Spanish social services system is in a state of collapse, as has also been claimed in other studies [28], due to constant cutbacks in social spending [11]. The resulting erosion of the social services has led to retrogression, as has been noted in other studies [10]. Social workers in this and other studies [13] agree that the Spanish social services present a lack of development or progress.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…According to participants, the Spanish social services system is in a state of collapse, as has also been claimed in other studies [28], due to constant cutbacks in social spending [11]. The resulting erosion of the social services has led to retrogression, as has been noted in other studies [10]. Social workers in this and other studies [13] agree that the Spanish social services present a lack of development or progress.…”
Section: Discussionsupporting
confidence: 75%
“…Various authors have drawn attention to the erosion and even collapse of the so-called welfare states due to changes in public social policies [9][10][11]. The problems generated by these measures cause welfare states to face high rates of poverty and inequality [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Our first social policy article, by Leanne Giordano, Dr. Michael Jones, and Dr. David Rothwell (), reviews the public policy literature on economic inequality in wealthy countries, focusing on research published from 2008 to 2018. The authors demonstrate that interest in inequality grew over this time frame.…”
Section: Public Policy Research Retrospective Review Articlesmentioning
confidence: 99%
“…In the social policy and related literature, there have been relatively fewer studies of cross-national differences in household wealth (Giordono, Jones, & Rothwell, 2019). The extant literature has found that wealth and income are far from perfectly correlated and that wealth inequality is more pronounced than income inequality (Balestra & Tonkin, 2018;Cowell, Karagiannaki, & McKnight, 2018;Killewald, Pfeffer, & Schachner, 2017;Saez, 2017).…”
Section: Introductionmentioning
confidence: 99%